INTEGRATED SOURCE ROCK ANALYSIS TO UNDERSTAND SHALE GAS POTENTIAL OF TALANGAKAR AND LEMAT FORMATIONS, SOUTH SUMATRA BASIN - EKANINGGARANI, FEBRIE
Shale gas booming in United States which was pioneered by Barnett Shale in 2000-ies had triggered most countries to find out the potential in their own areas, included Indonesia. Several studies have been conducted. IHS stated that shale gas potential in Indonesia could reach 5.000 TCF with six main plays, one of them is Talangakar Formation in South Sumatra Basin. The area of study is located in PT Medco E&P Indonesia contract area and surroundings. Objects of study are Tertiary deposits of Lemat and Talangakar Formation that already proven as source rocks. The objective is to understand shale gas potential qualitatively from integrated source rock analysis using literature, well data, and interpreted maps. There are two methods which were applied in the study, Passey method and probabilistic multimineral. Passey method was applied to know the vertical continuity of organic richness in a well, using combination of resistivity and sonic logs. The results then were calibrated to TOC laboratory analysis from rock samples. Multimineral method was attempted to know mineral volume, especially clay and quartz content which are crucial to know the brittleness. Contrary to the deterministic computation of the standard interpretation, multimineral uses a probabilistic approach to estimate the volume of constituents in the formation. The method then was calibrated by XRD data from rock sample. Objects of study are divided into three intervals based on stratigraphic position, lithology characteristic and well logs pattern become Upper Talangakar, Lower Talangakar, and Lemat Intervals. These intervals then were being correlated and analyzed to get TOC, clay, and quartz content. In the practical, Passey method can be applied into 21 wells while multimineral method only get succeed in four wells due to limited well log data but all calibration from both methods show pretty good match. After that, all value then integrated into a map to find out shale gas potential area. Shale gas rank was generated and compared to Barnett Shale. Analysis results show that shale gas potential in South Sumatra Basin in not too attractive, compared to Barnett Shale. Most of TOC value in gas window area ranges from 1-2% with high clay and low quartz content. These indicate that shale gas potential in area of study is not quite big and rather difficult to be produced using recent technology. Lower Talangakar Interval, which has 21 point, is the best interval for shale gas potential due to large extent and fairly high brittleness value. Lematang Deep is the most attractive subgraben for further analysis due to gas window maturity of all intervals, good to very good TOC quality, and high brittleness value. But regionally, high organic content area lies on oil window maturity so probably it would be more potential for oil shale.